2020
DOI: 10.1177/1359105320937055
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative lifetime stress exposure predicts greater impulsivity and addictive behaviors

Abstract: The study investigated whether lifetime stress exposure is associated with greater impulsivity and addictive behavior. We also examined whether stress and impulsivity interactively predicted food addiction and alcohol-related behavior. Greater lifetime stress exposure was related to more impulsivity and food addictive behaviors, but not alcohol-related consequences. There were no interactions between lifetime stress exposure and impulsivity in predicting addictive behaviors. Exploratory analyses revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 59 publications
3
18
0
1
Order By: Relevance
“…This study adds timely data to existing literature on the role of stress in decision making and consequential behaviours. Similar to previous research that documented associations between stress and delay discounting (Diller et al., 2011) and maladaptive behaviours, such as substance use and food addiction (McMullin et al., 2020; Sinha, 2008), we found that stress was positively related to delay discounting and stockpiling, and stress was negatively related to physical distancing during the COVID‐19 pandemic. These findings highlight stress reduction as a potential avenue for managing behaviours that have the potential to impact both individual and public health and well‐being.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study adds timely data to existing literature on the role of stress in decision making and consequential behaviours. Similar to previous research that documented associations between stress and delay discounting (Diller et al., 2011) and maladaptive behaviours, such as substance use and food addiction (McMullin et al., 2020; Sinha, 2008), we found that stress was positively related to delay discounting and stockpiling, and stress was negatively related to physical distancing during the COVID‐19 pandemic. These findings highlight stress reduction as a potential avenue for managing behaviours that have the potential to impact both individual and public health and well‐being.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, stress is associated with amplified tendencies for selecting immediate gratification with smaller benefits rather than waiting for larger benefits in the future (Diller et al., 2011), a tendency referred to as delay discounting. Studies have also established a link between stress and risk for maladaptive behaviours, such as substance use and food addiction (McMullin et al., 2020; Sinha, 2008). Furthermore, some researchers have found that delay discounting mediates the relationship between stress and substance use (Fields et al., 2009; Nikolova et al., 2016).…”
Section: Stress and Covid‐19 Related Behaviors: The Mediating Role Of Delay Discountingmentioning
confidence: 99%
“…ELA can be viewed as nonspecific because it predisposes individuals to a wide range of addictive behaviors. For example, in a sample of healthy young adults ( n = 200), greater lifetime stress exposure was related to increased impulsivity and FA [ 126 ], suggesting that food is a predictable go-to for self-medication [ 127 ]. A nationally representative sample of young adults’ ( n = 10,813) exposure to multiple forms of maltreatment predicted excessive sugar sweetened beverage consumption [ 128 ].…”
Section: Trauma and Ptsdmentioning
confidence: 99%
“…There were significant correlations between stress and internet use and smartphone use, and these associations were well shown in regression analysis. Stress is thought to play a role in the development of addiction by increasing craving and motivation toward the addictive behavior [ 42 ]. The association between stress and addictive behaviors may be bidirectional; such addictive behaviors may be used as a means of reducing stress, and blunted stress responses may confer an increased risk of engaging in addictive behaviors [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stress is thought to play a role in the development of addiction by increasing craving and motivation toward the addictive behavior. 42 The association between stress and addictive behaviors may be bidirectional; such addictive behaviors may be used as a means of reducing stress, and blunted stress responses may confer an increased risk of engaging in addictive behaviors. 42 On the other hand, in the regression analysis, there were no association was observed between alcohol and stress as in the previous study, 7 and this was the same in correlation analysis.…”
Section: Associations Between Stress and Internet Smartphone And Alco...mentioning
confidence: 99%